Approach to tune drug release in particles fabricated from methacrylate functionalized polylactides. Issue 3 (25th January 2021) - Shavkuta, Boris; Bardakova, Kseniia; Khristidis, Yana; Minaev, Nikita V.; Frolova, Anastasia; Kotova, Svetlana; Aksenova, Nadezhda; Heydari, Zahra; Semenova, Elena; Khlebnikova, Tatyana; Golubeva, Elena N.; Kostjuk, Sergei; et al.
Abstract : Different particles' mechanical properties and surface topography that significantly influenced the degradation rate, drug loading, and release. Abstract : The development of thermolabile substance carriers with a variable shape, size, and release kinetics is one of the most difficult goals of the pharmaceutical industry. Here, we propose to use the two-step combination of two-photon polymerization (2PP) and micromolding techniques to fabricate particles of a preset shape and size from star-shaped methacrylate functionalized poly(d, l )-lactides. Using a 2PP set-up, we fabricated an E-Shell cube-patterned matrix used to prepare a silicon mold. Then this mold was filled with functionalized poly(d, l )-lactides mixed with 4, 4′-bis(dimethylamino)benzophenone as a photoinitiator and exposed to UV irradiation to crosslink particles which were further easily detached. The study revealed that the arm length of the functionalized polylactides caused differences in the mechanical properties and surface topography of the fabricated particles that determined their degradation rate, drug loading and release. Using the arm length as a structure parameter, one can prepare tailored polylactide particles with controllable substance release.